Adobe photoshop 6.0 for photographers : - Evening, Martin (Focal Press, 2001)
Adobe Photoshop 6.0 for Photographers begins with an introduction to working with digital images, providing essential information on everything from scanning devices to color management and output issues. Practical workshops show you how to master the essential techniques, such as optimizing an image for prepress, color correction, retouching techniques, layers palette management, toning a black and white image, rendering textures and so on. Each technique is described in step-by-step detail, showing exactly which command to use, whether you're working with a Mac or PC.